Nurse training and completion of fluid balance chart documentation among patients with chronic kidney disease at Kiruddu National Referral Hospital. A cross-sectional study. - Harriet Margaret Muganga Namuganga; Dr. Grace Nakate (Student's Journal of Health Research Africa, 2026)
Background: Fluid overload is a common complication in CKD and requires accurate monitoring through fluid balance charts (FBCs). This study assessed the effectiveness of nurse training on completion of fluid balance chart documentation among patients with chronic kidney disease at Kiruddu National Referral Hospital. Methodology: A quantitative quasi-experimental (pre–post) study was conducted at Kiruddu National Referral Hospital. A total of 104 fluid balance charts were reviewed using convenience sampling. Data were collected using an audit checklist to assess documentation completeness before and after a nurse training intervention. Data were analyzed using descriptive statistics and a paired sample t-test to compare pre- and post-intervention results. Results: Pre-intervention findings showed poor documentation, with most variables scoring below 50%. Post-intervention results indicated significant improvement in documentation completeness. Patient identification details such as name and ward achieved 100% completion. Fluid intake improved from 0% to 88.5%, fluid output from 6.7% to 76%, and amount in milliliters from 40.4% to 94.2%. The paired t-test revealed a statistically significant improvement in documentation after training (t (103) =30.755, p